Poly-acrylic acid brushes and adsorbed proteins - Reinhardt, Matthias; Kreuzer, Martin; Geue, Thomas; Dahint, Reiner; Ballauff, Matthias; Steitz, Roland (Zeitschrift für physikalische Chemie, 2015)
Abstract Planar polyelectrolyte brushes are prepared by Langmuir-Schaefer - based grafting of perdeuterated (styrene)49-b-(acrylic - acid)222 block copolymer (dPS-b-PAA) to dPS pre-coated silicon - supports with grafting density σPAA from 0.07 to - 0.11 nm-2. The structure of the solvent-swollen brushes, - i. e. the volume fraction profile of polymer segments, ϕPAA, as a function of altitude z from the grafting - plane into the liquid phase is extracted from neutron reflectivity - measurements. We find that for all cases investigated - ϕPAA(z) resembles a Gaussian profile. Although very - condensed, the PAA brushes can be loaded with bovine serum albumin - (BSA). The integral amount of adsorbed BSA scales linearly with - grafting density. We compare our z-resolved volume fraction profile - ϕBSA(z) of BSA on PAA brushes with existing literature - on that system. It is found that a cross-over takes place in the - adsorption scheme from ternary compressive, where proteins can - approach the grafting surface only by compressing the brush, to - ternary insertive, where proteins enter the brush with only local - perturbation of the concentration profile, as a function of - RP/Hmax, where RP is the - Stokes-Radius of the protein, and Hmax is the - experimentally determined maximum height of - the brush.